2019
DOI: 10.1158/0008-5472.can-18-2965
|View full text |Cite
|
Sign up to set email alerts
|

The Critical Role of RNA m6A Methylation in Cancer

Abstract: Since the identification of the first RNA demethylase and the establishment of methylated RNA immunoprecipitationsequencing methodology 6 to 7 years ago, RNA methylation has emerged as a widespread phenomenon and a critical regulator of transcript expression. This new layer of regulation is termed "epitranscriptomics." The most prevalent RNA methylation, N 6-methyladenosine (m 6 A), occurs in approximately 25% of transcripts at the genome-wide level and is enriched around stop codons, in 5 0-and 3 0-untranslat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
522
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 582 publications
(528 citation statements)
references
References 77 publications
5
522
1
Order By: Relevance
“…Recent years have witnessed remarkable advancements of m 6 A modification in regulating all stages of the RNA life cycle. The deposition of m 6 A is encoded by "writers" that catalyze m 6 A formation (such as METTL3, METTL14, and WTAP), "erasers" that selectively remove the m 6 A code (such as FTO and ALKBH5), and "readers" that decode m 6 A methylation (such as YTH domain proteins and IGF2BP) [42]. m 6 A has been demonstrated to affect the targeted mRNA or miRNA and participate in the progression of various cancers [43].…”
Section: Discussionmentioning
confidence: 99%
“…Recent years have witnessed remarkable advancements of m 6 A modification in regulating all stages of the RNA life cycle. The deposition of m 6 A is encoded by "writers" that catalyze m 6 A formation (such as METTL3, METTL14, and WTAP), "erasers" that selectively remove the m 6 A code (such as FTO and ALKBH5), and "readers" that decode m 6 A methylation (such as YTH domain proteins and IGF2BP) [42]. m 6 A has been demonstrated to affect the targeted mRNA or miRNA and participate in the progression of various cancers [43].…”
Section: Discussionmentioning
confidence: 99%
“…Research aimed at uncovering the mechanism has shown that m6A serves as a regulator in cancer [156,157].…”
Section: Therapeutic Strategy Based On M6amentioning
confidence: 99%
“…In the last few years, several studies have placed RNA modifications in the forefront of cancer research [36,38,64,66,77], mostly focused on the machinery responsible for writing and erasing m6A modifications. For many years, FTO was thought to be of special interest due to its association with obesity [78].…”
Section: Discussionmentioning
confidence: 99%
“…However, this is now thought to be incorrect, as later studies showed that FTO is in fact an eraser of N6,2'O-methyladenosine (m6Am), which is much less abundant in mRNAs [28,80]. Similarly, FTO has been proposed to constitute a promising target for antitumor therapies [38,81,82]. While FTO has been shown to play an important role in leukaemia [81], it is possible that additional RMPs such as HENMT1, which is drastically dysregulated in this cancer type, might constitute a better drug target to inhibit leukemogenesis (Figure 4).…”
Section: Discussionmentioning
confidence: 99%